2019
DOI: 10.3390/ph12010040
|View full text |Cite
|
Sign up to set email alerts
|

Physical Stability and Viscoelastic Properties of Co-Amorphous Ezetimibe/Simvastatin System

Abstract: The purpose of this paper is to examine the physical stability as well as viscoelastic properties of the binary amorphous ezetimibe–simvastatin system. According to our knowledge, this is the first time that such an amorphous composition is prepared and investigated. The tendency toward re-crystallization of the amorphous ezetimibe–simvastatin system, at both standard storage and elevated temperature conditions, have been studied by means of X-ray diffraction (XRD). Our investigations have revealed that simvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Simvastatin is obtained by fermentation of Aspergillum terreus , which is a fungi, in the form of inactive lactone, which is further hydrolyzed to active β-hydroxy acid and works as an anti-hyperlipidemic agent by inhibiting HMG-CoA reductase enzyme, which has been well-established in a human clinical trial [ 9 ]. Simvastatin is among the most potent statin and has been listed among the top five frequently prescribed medicines for reducing high cholesterol [ 10 , 11 ]. Apart from its role as anti-hyperlipidemic agent, its pleiotropic effects opens a totally new horizon in medical sciences, suggesting its anti-tumor [ 12 ], anti-cancer [ 13 ], cardio-protective [ 14 ], anti-inflammatory, immune-modulatory, and anti-diabetic potential [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin is obtained by fermentation of Aspergillum terreus , which is a fungi, in the form of inactive lactone, which is further hydrolyzed to active β-hydroxy acid and works as an anti-hyperlipidemic agent by inhibiting HMG-CoA reductase enzyme, which has been well-established in a human clinical trial [ 9 ]. Simvastatin is among the most potent statin and has been listed among the top five frequently prescribed medicines for reducing high cholesterol [ 10 , 11 ]. Apart from its role as anti-hyperlipidemic agent, its pleiotropic effects opens a totally new horizon in medical sciences, suggesting its anti-tumor [ 12 ], anti-cancer [ 13 ], cardio-protective [ 14 ], anti-inflammatory, immune-modulatory, and anti-diabetic potential [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, co-amorphous drug delivery systems have aroused wide attention for stabilizing neat amorphous drugs and providing solubility/dissolution advantages (such as the faster dissolution rate and enhanced supersaturation ability) over corresponding crystalline and amorphous drugs [ 10 ]. A co-amorphous system is prepared by amorphizing a drug and a small molecule excipient (e.g., glibenclamide-arginine [ 11 ] and griseofulvin-tryptophan [ 12 ]) or a drug and another drug (e.g., docetaxel-bicalutamide [ 13 ] and ezetimibe-simvastatin [ 14 ]), to form a single amorphous phase in a certain stoichiometric ratio. In addition, a co-amorphous drug delivery system has become an effective alternative strategy to overcome the limitations of amorphous solid dispersion (ASD).…”
Section: Introductionmentioning
confidence: 99%
“…Although for e, two distinct carbon signals can be observed for the initial amorphous form, indicative of two predominant orientations, just one signal can be observed in the second MAS period, where the change to the crystalline phase has already begun. Knapik‐Kowalczuk et al [ 27 ] already showed by differential scanning calorimetry (DSC) that quench‐cooled, amorphous EZI has a glass transition at approximately 64°C as the only thermal event, which is approximately 30 K higher than the calibrated sample temperature during MAS. To further exclude temperature as the origin of the observed changes, amorphous EZI was stored in an oven at 40°C for 48 h. Subsequent analysis by XRPD confirmed the amorphicity of the sample (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…After 88 days, an additional 1 H‐ 13 C FSLG HECTOR NMR spectrum with the same resolution in the indirect dimension revealed changes in the 1 H NMR chemical shifts. Górniak et al [ 28 ] and Knapik‐Kowalczuk et al [ 27 ] already showed by DSC that EZI has only one endothermic peak at 164°C, [ 28 ] which corresponds to the melting point, making changes due to elevated temperatures unlikely. A comparison of XRPD powder patterns (Figure 6) of EZI before MAS, which should represent the state of the initial 1 H‐ 13 C FSLG HECTOR NMR spectrum, and after MAS, representing the new spectrum, showed no differences in peak positions, so no completely new phase of EZI has formed.…”
Section: Resultsmentioning
confidence: 99%